Impact of COVID-19 on Pregnancy and Childbirth: A Systematic Review of Recent Evidence - Mir Ibrahim Sajid; Sheharbano Awais; Khizar Sala; Maryam Sherwani; Sajid Abaidullah; Nighat Kamal; Zahida Parveen (BioMedica, 2020)
Background and Objective: There is a high suspicion that SARS-CoV-2 might be transmitted vertically from mother to fetus and causes clinically significant infection. This review evaluates the pathogenesis, risk factors, diagnosis and management strategies in pregnant women suspected or confirmed with COVID-19 infection. Methods: A literature review of published articles was carried out using keywords of corona virus (and its root derivatives), pregnancy, vertical transmission and childbirth in Medline, Cochrane, CINAHL and Web of Sciences. Clinical articles including case-control, case reports, case series and reviews published between 2019 and 2020, in English language were included. Editorials and Letter to Editors were not included. Two independent authors reviewed title and abstract and another set of two independent authors screened full text. A total of 22 articles were shortlisted for addition into the final manuscript. Results: A total of 403 pregnancies were considered in the study with most of the patients in the third trimester of pregnancy. There was no maternal mortality reported in the literature, however 1.49% fetal mortality has been reported. Conclusion: Extensive care should be taken to determine the timing and mode of delivery, preparation of a safe-to-deliver labor room and the choice of anesthesia with detailed newborn observation.